Reassessing gender and achievement : questioning contemporary key debates - Francis, Becky (Routledge, 2005)
This new and topical book, written by editors of the international journal Gender and Education and aimed at educational professionals, draws together the findings and arguments from the wealth of material available on gender and achievement.